2013
DOI: 10.1680/gein.13.00004
|View full text |Cite
|
Sign up to set email alerts
|

Performance of nonwoven geotextile-reinforced walls under wetting conditions: laboratory and field investigations

Abstract: The first geosynthetic retaining wall in Brazil was constructed in 1984 as an instrumented 10 m high geotextile-reinforced soil wall with a poorly draining backfill. This structure has been showing excellent performance throughout its service life, even after long periods of rainfall. In the past, the excellent performance of the wall had been attributed to the influence of soil confinement on the geotextile strength properties as well as the comparatively high interface shear strength between the fine soil an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 21 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…However, results reported in these studies seem to indicate that in fine-grained soils, the added drainage capability of a geocomposite could more than compensate the interlocking hindrance due to the existence of a nonwoven geotextile, which is consistent with the findings of other related studies on marginal quality soils (e.g. Zornberg and Mitchell 1994;Mitchell and Zornberg 1995;Portelinha et al 2013aPortelinha et al , 2013b. Khoury et al (2011) used a modified direct shear apparatus to study the effect of matric suction on soilgeotextile interface behaviour.…”
Section: Introductionsupporting
confidence: 90%
“…However, results reported in these studies seem to indicate that in fine-grained soils, the added drainage capability of a geocomposite could more than compensate the interlocking hindrance due to the existence of a nonwoven geotextile, which is consistent with the findings of other related studies on marginal quality soils (e.g. Zornberg and Mitchell 1994;Mitchell and Zornberg 1995;Portelinha et al 2013aPortelinha et al , 2013b. Khoury et al (2011) used a modified direct shear apparatus to study the effect of matric suction on soilgeotextile interface behaviour.…”
Section: Introductionsupporting
confidence: 90%
“…The GTX ( Figure 2C) consists of mechanically bonded (needle punched) continuous filaments of polypropylene. Several laboratory and field studies have shown the beneficial effect of using non-woven geotextiles as reinforcement elements of fine-grained soils (poorly draining soils) due to their internal drainage capacity (Tan et al, 2001;Portelinha et al, 2013). Indeed, the hydraulic properties of non-woven geotextile reinforcements can assist in the pore-water pressure dissipation, hence improving the internal stability of the reinforced structure.…”
Section: Geosyntheticsmentioning
confidence: 99%
“…Despite the problems arising from the use of poorly draining backfill, some studies have reported excellent performance of GRSS constructed with fine-grained soils reinforced with nonwoven geotextiles (Tatsuoka and Yamauchi 1986;Benjamim et al 2007;Portelinha et al 2013). The hydraulic properties of nonwoven geotextiles can help to dissipate pore-water pressures, contributing to the internal stability of the structure (Ling et al 1993;Tan et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The hydraulic properties of nonwoven geotextiles can help to dissipate pore-water pressures, contributing to the internal stability of the structure (Ling et al 1993;Tan et al 2001). As the reinforcement layers are able to provide internal drainage, the drainage capacity of the backfill is increased (Portelinha et al 2013).…”
Section: Introductionmentioning
confidence: 99%